THE APPLICATION OF “DHAMMIC SOCIALISM” BY BUDDHADASA BHIKKHU'STOWARD LOCAL GOVERNANCE FOR ADMINISTRATORS OF SUB-DISTRICT ADMINISTRATION ORGANIZATION IN SURATTHANIPROVINCE - Yoodee, Seksak; Lapi-e, Aussiri; Puakkong, Chaiwat (Journal of Buddhist Anthropology, 2022)
The Objectives of this research article were to 1) Administrator opinion of sub-district administration organization in suratthani province toward application of “DHAMMIC Socialism” according to local governance based on Sangahavatthu 4 and PAMS – POSDCoRB concept. and 2) Propose guidline for application of “DHAMMIC Socialism” according to local governance for sub-district administration organization in suratthani province. It was developed as mixed-methodology research. The sample used in quantitative research were population 388 peoples of administrator of sub-district administration organization and were selected of simple random sampling amount 312 samples. Data was collected from questionnaire and analyzed by statistical treatment such as mean and standard deviation. Sample of 7 key informants were selected of purposive sampling as quanlitative research. Data retrieved from in-depth interview and analyzed by analytic induction. The results were 1) overall opinion of administrator of sub-district administration organization in suratthani province toward application of “DHAMMIC Socialism” according to local governance based on Sangahavatthu 4 was at a high level. Considering each aspect ordered from the highest to the least, they were Atthajariya, Piyawaja, Then and Samanatta respectively. While overall opinion of administrator of PAMS – POSDCoRB concept was at a high level. Considering each aspect ordered from the highest to the least, they were society, morality, public policy and authority respectively. 2) the/proposes/that application of DHAMMIC/Socialism” according/to/local governance for sub-district administration organization in suratthani province should be mechanical drive to executives base on benefit sharing and creating equality in social justice as fairness.